2001
DOI: 10.1038/sj.ijo.0801621
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and determinants of physical activity in obese and non-obese children

Abstract: OBJECTIVE:To compare the physical activity (PA) patterns and the hypothesized psychosocial and environmental determinants of PA in an ethnically diverse sample of obese and non-obese middle school children. DESIGN: Cross-sectional study. SUBJECTS: One-hundred and thirty-three non-obese and 54 obese sixth grade children (mean age of 11.4 AE 0.6). Obesity status determined using the age-, race-and gender-speci®c 95th percentile for BMI from NHANES-1. MEASUREMENTS: Objective measurements were collected of PA over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
386
14
20

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(459 citation statements)
references
References 34 publications
39
386
14
20
Order By: Relevance
“…The absence of an association found for all children between overweight or obesity and physical activity practice (unlike previously reported (30,31) ) may be partly explained by our procedure of measurement of physical activity that was based on selfreported information and that did not take into account the intensity of physical activity.…”
Section: Discussionmentioning
confidence: 55%
“…The absence of an association found for all children between overweight or obesity and physical activity practice (unlike previously reported (30,31) ) may be partly explained by our procedure of measurement of physical activity that was based on selfreported information and that did not take into account the intensity of physical activity.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, population-based studies have consistently shown that overweight/obese children have higher levels of BP and a higher prevalence of hypertension than their non-overweight/obese counterparts. [9][10][11] Given that sedentary behaviours are positively associated with childhood adiposity, [12][13][14] it is reasonable to hypothesize that various sedentary activities may also be independently associated with BP in children.…”
Section: Introductionmentioning
confidence: 99%
“…10 In contrast, several studies reported no or a positive association, whereas others reported inverse associations, but not always consistently for systolic and diastolic BP in both males and females. 11,13 Moreover, although many studies have examined the association between physical activity and adiposity in younger children, 14,15 very few large population-based studies (and none conducted in Australia to date) have assessed the relationship with BP during prepuberty.…”
Section: Introductionmentioning
confidence: 99%